Advertising quality and market share - Πέκκα - Οικονόμου Βικτωρία; Σολδάτος Γεράσιμος Θ. (SPOUDAI Journal of Economics and Business, 1999)
This paper utilizes a signaling-game approach to advertising and concludes that advertising is a means of increasing profits and not an instrument of consumer preferences manipulation. It also concludes that advertised brands should offer to the consumer something original and if not, then offer what more or less the rival do.